One hundred years of solitude - Márquez Gabiel García
Famously associated with the term ‘magical realism’, Marquez is probably South America’s most famous literary export. Equally tragic, joyful and comical, One Hundred Years of Solitude inhabits a strange dream-like space where very little makes real sense, but everything is mysteriously and vividly alive nonetheless. Blending fantasy and reality seamlessly, the characters struggle hopelessly against a merciless backdrop of madness, corruption and death…all measured out equally with farce and fatality; as profound a statement on the human condition as possible. In every sense, this is literature on the grandest of scales. An acknowledged masterpiece, this is the story of seven generations of the Buendía family and of Macondo, the town they have built. Though little more than a settlement surrounded by mountains, Macondo has its wars and disasters, even its wonders and miracles. A microcosm of Columbian life, its secrets lie hidden, encoded in a book and only Aureliano Buendía can fathom its mysteries and reveal its shrouded destiny. Blending political reality with magic realism, fantasy with comic invention, One Hundred Years of Solitude is one of the most daringly original works of the twentieth century.